1998
DOI: 10.3109/01480549809017849
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gaba Receptor Complex in Low Dose Lindane (HCH) Induced Neurotoxicity: Neurobehavioural, Neurochemical and Electrophysiological Studies

Abstract: Lindane is widely used as an insecticide and scabicide in mammals. High doses in chronic exposures caused hyperexcitability and convulsions and impaired motor activity involving GABA-ergic mechanism. To investigate the role of GABA/Benzodiazepine mechanism in the neurotoxicity of low doses of lindane, rats were administered 2, 3, or 5 mg/kg orally for 90 days and behavioural, electrophysiological, and neurochemical studies were conducted. The animals exposed to lindane exhibited increased geotaxis and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…It may be of prolonged duration (years) and is exceedingly prevalent among chemical workers chronically exposed, with up to 67% variably affected in some studies 69–71. In laboratory animals, OCPs may reduce brain GABA concentrations72 and bind to and inhibit the GABA(A) receptor in the brain,73–75 the same receptor complex that has been implicated in the etiology of ET 56. In dogs, some OCPs produce parenchymatous degeneration in the cerebellar cortex,76 the brain region which may be involved in the pathogenesis of ET 36–38…”
Section: Nature Vs Nurturementioning
confidence: 99%
“…It may be of prolonged duration (years) and is exceedingly prevalent among chemical workers chronically exposed, with up to 67% variably affected in some studies 69–71. In laboratory animals, OCPs may reduce brain GABA concentrations72 and bind to and inhibit the GABA(A) receptor in the brain,73–75 the same receptor complex that has been implicated in the etiology of ET 56. In dogs, some OCPs produce parenchymatous degeneration in the cerebellar cortex,76 the brain region which may be involved in the pathogenesis of ET 36–38…”
Section: Nature Vs Nurturementioning
confidence: 99%
“…In zebrafish, it has been reported that ethanol causes abnormal development of motor neurons and muscle fibers [25]. The neurotoxic effect of lindane has also been well documented [26], [44] and chronic exposure of low dose lindane causes neurobehavioral, neurochemical, and electrophysiologrcal efects in rat brain [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms underlying the lindane seizures have been proposed [8] . First of all, lindane binds to the picrotoxin site within the GABA A chloride channel and suppresses the transmembrane influx of chloride ions [6,7] . Further, it has been postulated that lindane could produce its neurotoxic effects through intracellular mobilization of calcium from the dantrolene-sensitive pools and calcium influx [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Seizures are one of the first and main manifestations of the neurotoxic effects of lindane in humans and animals [4,5] . Lindane evokes seizures mainly through the blockade of the ␥ -aminobutyric acid A (GABA A ) receptor complex [6][7][8] . Lindane-induced seizures are refractory to numerous classical and novel antiepileptic drugs [9] .…”
Section: Introductionmentioning
confidence: 99%